Pengaruh Kompetensi Profesional terhadap Kinerja Guru Sekolah Dasar di Kecamatan Maospati, Kabupaten Magetan - Purwo Purwo (Cipta Media Harmoni, 2025)
The reality that is a problem among elementary school teachers today includes teachers who are less professionally competent. Teachers in the field still do not have adequate learning tools and also lack responsibility to address personality issues that can contribute to student success. The purpose of this study is to assess the level of competence and performance of elementary school teachers and measure the level of influence of professionalism on the performance of elementary school teachers in Maospati District, Magetan Regency. This study is quantitative descriptive using an ex post facto methodology by measuring the influence of professional competence and performance on elementary school teachers in Maospati District with a sample of 63 people. The analysis technique used with simple linear regression. The test results showed (t=3.507; Sig.=0.001) that there was a positive and significant influence of teachers' professional competence on the performance of elementary school teachers in Maospati District. There is still a need to increase the mastery of technology-based learning media innovations to be able to improve professional competence so that it can improve the performance of elementary school teachers in Maospati District. The results of the study concluded that the performance of elementary school teachers in Maospati District was significantly influenced by the level of professional competence they had. There are still high opportunities for other competencies that have a high relationship or influence on the performance of elementary school teachers in Maospati District .